Serum and blister‐fluid elevation and decreased epidermal content of high‐mobility group box 1 protein in drug‐induced Stevens–Johnson syndrome/toxic epidermal necrolysis. (26th March 2019) - Carr, D.F.; Wang, C.‐W.; Bellón, T.; Ressel, L.; Nwikue, G.; Shrivastava, V.; Bergfeld, W.; Jorgensen, A.L.; Chung, W.‐H.; Pirmohamed, M.
Summary: Background: High‐mobility group box 1 (HMGB1) is a damage‐associated molecular‐pattern protein. Stevens–Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) are serious, immune‐mediated skin‐blistering conditions. Objectives: To determine serum and/or blister‐fluid total HMGB1 levels in SJS/TEN cohorts, and HMGB1 expression in formalin‐fixed, paraffin‐embedded (FFPE) SJS/TEN skin vs. healthy and maculopapular exanthema (MPE) skin. Methods Serum HMGB1 was quantified in Malawian nevirapine‐induced hypersensitivity, Taiwanese SJS/TEN and Spanish SJS/TEN cohorts. FFPE skin (healthy skin, MPE, SJS/TEN) was stained and assessed for HMGB1 expression. Results: Serum total HMGB1 was not significantly elevated in patients with nevirapine‐induced SJS/TEN (3·98 ± 2·17 ng mL −1 ), MPE (3·92 ± 2·75 ng mL −1 ) or drug reaction with eosinophilia and systemic symptoms (4·73 ± 3·00 ng mL −1 ) vs. tolerant controls (2·97 ± 3·00 ng mL −1 ). HMGB1 was significantly elevated in Taiwanese patients with SJS/TEN, highest during the acute phase (32·6 ± 26·6 ng mL −1 ) vs. the maximal (19·7 ± 23·2 ng mL −1 ; P = 0·007) and recovery (24·6 ± 25·3 ng mL −1 ; P = 0·027) phases. In blister fluid from Spanish patients with SJS/TEN, HMGB1 (486·8 ± 687·9 ng mL −1 ) was significantly higher than in serum (8·8 ± 7·6 ng mL −1 ; P <0·001). Preblistered SJS/TEN skin showed decreased epidermal nuclear HMGB1 expression in upper epidermis vs. healthy or MPE skin but retained basal/suprabasal expression. Conclusions: Epidermal HMGB1 expression was decreased in SJS/TEN skin. Retained basal/suprabasal epidermal HMGB1 expression may exacerbate localized injury in SJS/TEN. Abstract : What's already known about this topic? High‐mobility group box 1 (HMGB1) is a marker of tissue injury and innate immune response. Elevation of serum HMGB1 in patients with serious cutaneous adverse drug reactions has been reported previously. To date, no analysis of HMGBI distribution in Stevens–Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) patient blister‐fluid and skin biopsy tissue has been described. What does this study add? This study confirms serum HMGB1 elevation in SJS/TEN in three independent cohorts. It reports, for the first time, super‐elevation of HMGB1 in blister fluid and significantly decreased epidermal expression in preblistered SJS/TEN skin with suprabasal retention. These results are highly distinct from healthy or maculopapular exanthema skin and may represent a viable diagnostic tool. Linked Comment:  Dodiuk‐Gad. Br J Dermatol 2019; 181 :18–19 . Plain language summary available online Respond to this article